Business economics : decision-making and the firm - Brewster, David (London : The Dryden Press, 1997)
This book is about: The market environment; The firm in theory and practice; Production and costs analysis; Demand and revenue analysis; Pricing decisions; ...
Keywords: Economics; Business; Economics; Business; Business -- Decision making